Evidence of Melt Reaction Between Poly(3‐Hydroxybutyrate‐co‐3‐Hydroxyhexanoate) and Epoxidized Natural Rubber as Investigated by DSC, Isothermal TGA and FTIR Analyses. Issue 1 (July 2016) - Salim, Yoga Sugama; Saiter, Jean‐Marc; Natarajan, Valliyappan David; Kumar, Sudesh; Neon, Gan Seng; Han, Chan Chin
Summary: This work describes properties of a new polymeric system obtained after melt reaction between poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyhexanoate) [P(3HB‐ co ‐3HHx)] with 40% (in mass) of epoxidized natural rubber (ENR). Differential scanning calorimetry (DSC), thermogravimetry, infra‐red spectroscopy and confocal optical microscopy analysis were performed on this system. Before melt reaction, we found that ENR particles with diameters of more than 2 µm were homogeneously distributed in P(3HB‐ co ‐3HHx) phase using confocal optical microscope. From infrared spectroscopy, reaction engaged during the thermal cycle for sample preparation, leads to a melt reaction associated with inhibition of crystallization of P(3HB‐ co ‐3HHx) in the blend. This is also observed in DSC analysis. Furthermore, a progressive mass loss of up to 10% was observed after five half‐time of melt reaction by utilizing isothermal procedure in thermogravimetry.